Chitosan/Carboxymethylcellulose/Ionic Liquid/Ag(0) Nanoparticles Form a Membrane with Antimicrobial Activity - Camila Quadros; Vinícius W. Faria; Manuela P. Klein; Plinho F. Hertz; Carla W. Scheeren (Journal of Nanotechnology)
Silver metal nanoparticles were immobilized in chitosan/carboxymethylcellulose/BMI.BF4(1-n-butyl-3-methylimidazolium tetrafluoroborate ionic liquid) (CS/CMC/IL) to form polymeric membrane with 20 μm thickness. The CS/CMC/IL polymeric membrane was prepared using a simple solution blending method. Irregularly shaped Ag(0) nanoparticles with monomodal size distributions of 8.0±0.4 nm Ag(0) were immobilized in the membrane. The presence of small Ag(0) nanoparticles induced an augmentation in the CS/CMC/IL film surface areas. The CS/CMC/IL membrane containing Ag(0) showed increase antimicrobial activity the Ag(0) concentration increased up to saturation at 10 mg. CS/CMC/IL membrane that contains Ag(0) nanoparticles has enhanced durability of the membrane and exhibited stronger antimicrobial activity against Escherichia coli and Staphylococcus aureus.